43Dynamic atrioventricular delay achieves superior electrical synchrony when pacing both ventricles rather than left ventricle alone. (18th June 2020) - Thibault, B; Chow, A; Mangual, J; Badie, N; Waddingham, P; Mcspadden, L; Betts, T; Calo, L; Leyva, F
Abstract: Funding Acknowledgements: Abbott Introduction: Automatic adjustment of atrioventricular delay (AVD) with SyncAV has been shown to improve electrical synchronization when pacing one or two sites in the left ventricle together with the right ventricle. However, it is unknown if the same benefit can be gained by using SyncAV while pacing only the left ventricle without right ventricular pacing. Purpose:   Evaluate the acute improvement in electrical synchrony provided by SyncAV with and without MultiPoint Pacing (MPP) during biventricular (BiV) and LV only pacing. Methods:   Patients with LBBB and QRS duration (QRSd) ≥ 150 ms scheduled for CRT-P/D device implantation with quadripolar LV lead were enrolled in this prospective study. QRSd was measured post-implant from 12-lead surface electrograms by blinded experts during the following pacing configurations: intrinsic conduction, conventional BiV (BiV = RV + LV1), MPP (MPP = RV + LV1 + LV2), LV-only single-site (LVSS = LV1 only), and LV-only MPP (LVMPP = LV1 + LV2). For each pacing mode, SyncAV was enabled (e.g. BiV + SyncAV) with the patient-tailored SyncAV offset that minimized QRSd. As an additional reference, QRSd during BiV was also measured using the nominal static AVD (paced/sensed AVD = 140/110 ms). BiV and LVSS pacing used the latest activating LV cathode, whereas MPP and LVMPP used the two LV cathodes with the widest possible separation (>30mm). All configurations used the minimum programmable RV-LV and LV1-LV2 delays. Results:   Thirty-five patients (78% male, 33% ischemic, 26% ejection fraction, 165 ms intrinsic QRSd) completed device implant and QRSd assessment. Relative to intrinsic conduction, BiV with nominal AVD reduced the QRSd by 17.5% (p < 0.001 vs intrinsic). Enabling SyncAV with a patient-optimized offset significantly improved QRSd reduction. BiV + SyncAV reduced QRSd by 25.2% (p < 0.001 vs. BiV). The greatest QRSd reduction of 28.9% was achieved by MPP + SyncAV (p < 0.01 vs. BiV + SyncAV). Single- and multi-site LV-only pacing reduced QRSd significantly less than corresponding biventricular modes. LVSS + SyncAV reduced QRSd by 22.5% (p < 0.05 vs. BiV + SyncAV), and LVMPP + SyncAV reduced QRSd by 24.3% (p < 0.05 vs. MPP + SyncAV). As a percent of PR interval, optimal SyncAV offsets were similar for BiV + SyncAV (median: 13%, mean: 17%) vs. MPP + SyncAV (median: 13%, mean 16%, p = 0.35 vs. BiV + SyncAV), and similar for LVSS + SyncAV (median: 20%, mean: 28%) and LVMPP + SyncAV (median: 23%, mean: 26%, p = 0.35 vs. LVSS + SyncAV), but were significantly higher for LV-only settings vs. corresponding BiV/MPP settings (p < 0.01 for both pairs). Conclusion: Greater improvement in electrical synchrony using SyncAV was observed when right ventricular pacing was included with left ventricular pacing. Additional benefit was gained by the addition of a second left ventricular pacing site with MPP in combination with SyncAV in both biventricular and LV only pacing modes.